1980
DOI: 10.1021/jf60231a002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between agricultural chemicals and soil microflora and their effects on the degradation of [14C]parathion in a cranberry soil

Abstract: The interaction of selected fungicides, herbicides, and N-fertilizers with microorganisms in cranberry soils and their effects on the degradation of [phenyl-uC] parathion were investigated. Soil microorganisms were responsible for the oxidative as well as reductive degradation of the insecticide. Incubation of soils with parathion or p-nitrophenol for 4 days followed by the addition of [14C] parathion resulted after 24

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 16 publications
(26 reference statements)
0
32
0
Order By: Relevance
“…Two weeks after the last pretreatment, this soil was then treated with ['4C]insecticides in the same manner as the other six soils. Soils were moistened to field capacity (1/3-bar soil moisture tension) with distilled water and incubated at 25 OC in the dark by using a flow-through incubation system (Ferris and Lichtenstein, 1980). Air was periodically purged from the tightly sealed soil jars through both vapor and C02 traps, and this allowed maintenance of aerobic conditions and monitoring of [ 14C]insedicide degradation to ' T O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Two weeks after the last pretreatment, this soil was then treated with ['4C]insecticides in the same manner as the other six soils. Soils were moistened to field capacity (1/3-bar soil moisture tension) with distilled water and incubated at 25 OC in the dark by using a flow-through incubation system (Ferris and Lichtenstein, 1980). Air was periodically purged from the tightly sealed soil jars through both vapor and C02 traps, and this allowed maintenance of aerobic conditions and monitoring of [ 14C]insedicide degradation to ' T O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The enhanced biodégradation of some pesticides has been attributed to the substrate value of their degradation products (6)(7)(8). Degradation products of pesticides belonging to different classes such as phenoxyacetic acids, carbamothioates, N-methyl carbamates, and organophosphates have been reported to condition soils for rapid degradation of their respective parent compounds (Table II).…”
Section: Degradation Products As Inducers Of Pesticide Degradationmentioning
confidence: 99%
“…Hydrolytic reactions seem to play an important role in the initiation of pesticide metabolism by adapted soil microorganisms (13,14). In several instances, the presence of pesticide hydrolysis products has resulted in induction of a pesticide degrading population of soil microorganisms (6,7). In one of the first studies on the biodégradation of pesticides, Newman and Thomas (9) observed decreased persistence of 2,4-D in soils pretreated with its hydrolysis metabolite, 2,4-dichlorophenol.…”
Section: Degradation Products As Inducers Of Pesticide Degradationmentioning
confidence: 99%
“…However, little is known about the behavior of microbes concerned with the degradation of chemicals. The effect of chemicals as physiologically active substances on sediment/water 11,26,31,32) or soil 9,17,28) microflora has been well documented. However, there are few studies about how xenobiotic-degrading microorganisms act through the growth and metabolic processes.…”
mentioning
confidence: 99%